Decision to Purchase Hand Sanitizer During Covid-19 - Yulianingsih; Rachmat Gunawan; Muhammad Anjah Nurulloh; Danu Suryani (International Journal of Managemen Analytics (IJMA), 2023)
Hand sanitizer is one of the people's choices in preventing the transmission of Covid-19. The high demand for hand sanitizers is a business opportunity for hand sanitizer entrepreneurs in developing their businesses. The aim of this study; 1) to find out consumer responses regarding product quality, price, brand image and purchasing decisions; 2), analyze the effect of product quality, price and brand image simultaneously and partially on the decision to purchase handsanitizer at PT Gamajaya Global Grosir. The method used is multiple linear regression analysis with a total sample of 100 consumers. The results showed that 1) consumer responses regarding product quality, price, brand image and purchasing decisions were in good criteria; 2) product quality, price and brand image simultaneously and partially have a positive and significant effect on purchasing decisions on PT Gamajaya Global Grosir's hand sanitizer